Heat stress effects on the immune system of older adults: A systematic literature review - Rabab Awad; Assaf Suberry; Ahmad Abu-Akel; Liat Ayalon (Experimental Gerontology)
Objectives: We examined the evidence from experimental and cohort studies concerning the associations between heat stress and immune vulnerability in older adults. Research design and methods: A systematic search was performed in 6 academic databases, covering all papers that were published until April 2024. We included studies that explored immune-related outcomes associated with climate change, mainly heat shock, heat exposure, extreme temperature and global warming, among older adults, aged 65 and over. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for systematic reviews were followed to select the studies. Records that retained the exact same search terms from databases were imported into COVIDENCE software and were screened by two independent raters. Major findings were identified and synthesised. Results: Fifteen papers were considered eligible for full-text evaluation, and 4 papers met the inclusion criteria and were included in the analysis. Studies mainly point to age-related dysregulation in heat induced response of subgroups of interleukins and heat shock proteins (hsps). Discussion and implications: Heat stress may directly affect the regulatory function of older adults' immune system that plays a critical rule in the course of infections and inflammatory diseases. However, this review points to a paucity of relevant studies among older adults.